ISLAM SEBAGAI OBJEK STUDI DAN PENELITIAN: PENDEKATAN KEILMUAN DAN INOVASI METODOLOGIS - Wulandari; Sari, Elpita; Julhadi; Kamal, Tamrin; Hakim, Rosniati (LPPM STAI Muhammadiyah Probolinggo, 2024)
This research explores Islam as an object of study and research, with a focus on scientific approaches and methodological innovation. This study aims to understand how scientific methods and interdisciplinary approaches can be applied in research on Islam, as well as to evaluate methodological innovations that can improve the quality and relevance of research in this field. This research uses a qualitative approach with literature study methods and content analysis. This approach was chosen because this research aims to explore concepts, theories, and methodological innovations in Islamic studies in depth. Apart from that, this research also highlights the importance of using information and communication technology in Islamic research, especially in collecting, analyzing, and disseminating data. The research results show that an interdisciplinary approach and the use of technology can provide a more comprehensive and dynamic perspective in Islamic studies. This research concludes that methodological innovations, such as big data analysis, digital modeling, and participatory methods, have great potential to enrich Islamic studies and address contemporary challenges facing Muslims. Thus, this research makes a significant contribution to developing a more effective and relevant research methodology in Islamic studies. Keywords: Islamic Studies; Scientific Approach; Methodological Innovation; Interdisciplinary Approach.